Learning Culture from the Perspective of the Successful Indonesian Nurse Competency Examination - Hidayat, Syaifurrahman; Hannan, Mujib; Huzaimah, Nailiy; Suprayitno, Emdat; Mumpuningtias, Elyk Dwi; Putri, Prestasianita; Wijayanti, Agnes Erida; Manuel da Silva, Adão (Universitas Muhammadiyah Yogyakarta, 2024)
Background: The Indonesian Nurse Competency Examination (INCE) is a strategic component that determines the output of nursing graduate students. The varied geographical conditions of the various islands in Indonesia can influence access and quality of education, causing students to have a more inclusive perspective. The learning culture of Indonesian nursing students is unique and generally carries over to higher education, notably nursing profession education.Objective: The purpose of the study is to explain the learning culture model from the perspective of the success of the nurse competency examination and the relationship between learning culture and the success of the nurse competency examination.Methods: A qualitative and quantitative combination research (mixed method) with a sequential-exploratory design was employed. Stage 1 used descriptive qualitative methods. While data collecting used structured interviews, the sampling technique utilized snowball with (n=9), and data analysis used Sandelowski content analysis. Stage 2 was an observational analytical design with a retrospective approach involving 74 nursing students at Wiraraja University who lived in the Indonesian student area. Data analysis then employed the Structural Equation Model (SEM) test to find variables that significantly influence the success of INCE.Results: Stage-1 produced three themes: Theme-1: background of the learning environment concerning facilities utilization and searching strategy for learning resources; Theme-2: learning activities including learning styles, learning motivation, and self-confidence and abilities; Theme-3: learning habits comprising learning methods, concentration, and repeating the learning material. In stage 2, the result revealed that learning environment background (p=0.031), learning activities (p=0.021), and study habits (p=0.028) were significantly related to the success of the INCE on students.Conclusion: The learning culture of Indonesian students from the perspective of success in the INCE is formed starting from the pre-graduate level and continuing at the higher and professional levels.